Pelimpahan Kewenangan Peradilan Tata Usaha Negara ke Peradilan Umum atas Sengketa Pertanahan dengan Objek Sertipikat Tanah - Devi Anggita; Fitika Andraini (Jurnal Hukum Lex Generalis, 2025)
This study discusses the delegation of authority of the State Administrative Court (PTUN) to the general court regarding land certificate disputes, with a case study of Decision Number 20/G/2022/PTUN.SMG. The focus of this study is to analyze the legal basis, judges' considerations, and the legal implications of the delegation of authority. The research methods used are normative juridical and decision studies. The results of the study indicate that in this case, the land dispute that originated from the State Administrative decision was transferred to the general court because it was considered to involve civil aspects. However, this has given rise to a legal debate regarding the absolute jurisdiction between the PTUN and the general court. The findings of this study indicate the need for legal reform so that the authority of the judicial institution is clearer in handling overlapping disputed objects, especially regarding land certificates. This study recommends harmonization of regulations and legal understanding between judicial institutions to ensure legal certainty.